2019
DOI: 10.3390/ma12091480
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heavy Ion Irradiation on the Forward Dissolution Rate of Borosilicate Glasses Studied In Situ and Real Time by Fluid-Cell Raman Spectroscopy

Abstract: Borosilicate glasses are the favored material for immobilization of high-level nuclear waste (HLW) from the reprocessing of spent fuel used in nuclear power plants. To assess the long-term stability of nuclear waste glasses, it is crucial to understand how self-irradiation affects the structural state of the glass and influences its dissolution behavior. In this study, we focus on the effect of heavy ion irradiation on the forward dissolution rate of a non-radioactive ternary borosilicate glass. To create exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
4
10
0
Order By: Relevance
“…e α-irradiation increases leaching rate at different temperatures by no more than 3 times. is conclusion is consistent with recent data [53], where glass bombarded with 197 Au ions to simulate displacements from recoil nuclei was studied. e dissolution rate for the irradiated glasses in these tests increased by 3.7 ± 0.5 times which is assumed proportional to the rate of motion of leaching front.…”
Section: Effect Of Radiation On Leachingsupporting
confidence: 93%
See 1 more Smart Citation
“…e α-irradiation increases leaching rate at different temperatures by no more than 3 times. is conclusion is consistent with recent data [53], where glass bombarded with 197 Au ions to simulate displacements from recoil nuclei was studied. e dissolution rate for the irradiated glasses in these tests increased by 3.7 ± 0.5 times which is assumed proportional to the rate of motion of leaching front.…”
Section: Effect Of Radiation On Leachingsupporting
confidence: 93%
“…e dissolution rate for the irradiated glasses in these tests increased by 3.7 ± 0.5 times which is assumed proportional to the rate of motion of leaching front. It should be noted that the energy of gold ions is 945.6 MeV [53], while the energy of the recoil nuclei is close to 100 keV. Hence, in these experiments, the energy of particles initiating displacement cascades was overestimated by almost 10,000 times in comparison with actual conditions of α-decay in vitrified HLW.…”
Section: Effect Of Radiation On Leachingmentioning
confidence: 67%
“…Indeed, the α irradiation aging of the glass will cause significant changes in its structure and properties. ,, Due to the various complexities associated with handling and characterizing radioactive specimens, ion irradiation has been widely used as a proxy to simulate the effects of self-irradiation damage. It was recently observed in the literature that the alteration behavior of borosilicate glasses was significantly modified by the prior external irradiation by heavy ions, specifically, during the residual alteration rate regime. , Radiation damage was observed to result in an alteration layer around 4 times thicker than the one formed on a non-irradiated glass leached under the same conditions. The evolution of the leaching rate with irradiation dose was attributed to the effects of nuclear collisions, essentially, following the trend as observed in the structural and mechanical properties with nuclear dose.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the various complexities associated with handing and characterizing radioactive specimens, ion irradiation has been widely used as a proxy to simulate the effects of self-irradiation damage. It was recently observed in the literature that the alteration behaviour of borosilicate glasses was significantly modified by the prior external irradiation by heavy ions [22][23][24] , specifically, during the residual alteration rate regime 22,23 . Radiation damage was observed to result in an alteration layer around 4 times thicker than the one formed on a non-irradiated glass leached under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, it is contrary to the predominant assumption that corrosion studies on doped waste packages are most realistic. It is important to point out that recent ion irradiation studies have shown that radiation damage in glasses can increase the diffusion coefficient of water (by a factor of~20 31 ) and lead to an enhancement in the rate of forward dissolution (by a factor of~4 32 ). Whether mass transport through the pores plays any significant role in evaluating these factors has not been addressed yet.…”
Section: In the Supplementarymentioning
confidence: 99%